Multimedia educational manual "Auscultation of the lungs" - A. A. Garanin; A. O. Rubanenko; Yu. A. Trusov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The implementation of the basic principles of digital pedagogy is important for the modernization of educational activities at medical universities. One of the important steps of such modernization is to provide educational programs and disciplines implemented within their framework with a sufficient number of electronic and multimedia textbooks, including the most complex sections. One of such sections of the discipline "Propaedeutics of internal diseases" is lung auscultation. This section contains an extensive theoretical base, which may make it difficult to master this topic with a traditional approach to the educational process. In addition, in order to successfully master this skill, students need to perform independent lung auscultation in patients with various diseases of the respiratory system, which is not always achievable in real educational practice. Both theoretical and practical aspects of this patient examination method can be implemented in appropriate multimedia and electronic manuals, simulators and simulators. Conclusions. The manual "Lung Auscultation" developed at SamSMU can increase the efficiency of assimilation of the material, which will improve the formation of competencies among students, in terms of mastering the most important component of a physical examination of a patient – auscultation and aimed at a full-fledged examination of the patient, conducting a diagnostic search, interpreting the data obtained, making the correct diagnosis and prescribing optimal treatment.